2001
DOI: 10.1053/jlts.2001.24910
|View full text |Cite
|
Sign up to set email alerts
|

Technical challenges of hepatic venous outflow reconstruction in right lobe adult living donor liver transplantation

Abstract: A right lobe graft that is drained by the right hepatic vein (RHV) is obtained by transecting the liver on the right side of the middle hepatic vein (MHV). On occasion, a small RHV that only drains a portion of the right lobe, with the predominant outflow achieved by the MHV, is encountered. If such variation is not recognized while performing right lobe liver transplantation and the RHV only is used for reconstruction, venous outflow obstruction with subsequent graft congestion and eventual graft failure will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 18 publications
3
68
0
3
Order By: Relevance
“…Aside from the liver volume, it has been suggested that graft outflow drainage is of utmost importance in ensuring good immediate liver function. 7,22,23 Although the liver mass of the right lobe may be adequate, the venous outflow might be compromised, mainly because the anterior segments (V and VIII) are usually drained through the middle hepatic veins. Some investigators propose the preservation of the middle hepatic vein with the right graft to overcome this problem; however, this procedure may compromise donor safety, increasing the risk of the whole procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the liver volume, it has been suggested that graft outflow drainage is of utmost importance in ensuring good immediate liver function. 7,22,23 Although the liver mass of the right lobe may be adequate, the venous outflow might be compromised, mainly because the anterior segments (V and VIII) are usually drained through the middle hepatic veins. Some investigators propose the preservation of the middle hepatic vein with the right graft to overcome this problem; however, this procedure may compromise donor safety, increasing the risk of the whole procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called small-for-size syndrome (SFS) seems to be present in most series worldwide. This syndrome may have different aspects in its etiology: those related to the graft, such as size, actual functional mass, [3][4][5] or anatomic variability (presence of a significant branch, tributary of the middle hepatic vein) 6,7 ; those related to the recipient, such as metabolic status (diabetes, impaired renal function, etc), advanced disease stage (Child-Pugh score Ͼ9), and severity of portal hypertension 8 ; and finally, those related to the surgical technique, such as preservation of the middle hepatic vein with the graft (right liver), type of the right hepatic vein anastomosis with the vena cava, or the anastomosis of any significant branch (larger than 8 mm in diameter) also with the vena cava. [9][10] The relationship between the graft mass and the recipient's weight is very important in trying to prevent the incidence of the SFS.…”
mentioning
confidence: 99%
“…The graft is positioned orthotopically with a graft hepatic vein to recipient right hepatic vein orifice anastomosis or to a common trunk formed by the recipient's remnant left, middle, and right hepatic vein orifices (30,38). Middle hepatic venous branches draining segments V and VIII (45)(46)(47) (Figure 8) as well as accessory hepatic veins ≥5 mm in diameter are included in anastomoses either directly to the vena cava or through utilization of venous conduit. End-to-end anastomosis of the portal vein is frequently possible, as is the right hepatic artery to a suitable inflow source from the common hepatic artery.…”
Section: Creation Of Left Segment I-iv and Right Segment V-viii Graftsmentioning
confidence: 99%
“…In the case of rethrombosis, arterial reconstruction with an interposition graft (i.e., saphenous vein, sigmoid artery, or gastroepiploic artery) is recommended, rather than additional thrombectomy attempts. Presumably, such nonsurgical reasons as hemodynamic changes, hypercoagulable state, or infections are responsible for HAT, in 4,6,12,16,[19][20][21] addition to technical issues. In our experience, the incidence of HAT can be reduced by administration of prostacyclin during the early postoperative course.…”
Section: Vascular Complications Hepatic Artery Thrombosismentioning
confidence: 99%
“…Handling of the middle hepatic vein presents an immanent problem because it drains the right and left liver, with significant consequences for the donor and recipient. [15][16][17][18] To provide blood outflow and avoid graft congestion, it is necessary to preserve and anastomose all posterior hepatic veins with a diameter larger than 5 mm and the large branches of the middle hepatic vein responsible for drainage of the right anterior sector. Therefore, some centers favor inclusion of the entire middle hepatic vein in the right graft.…”
Section: Hepatic Venous Outflow Reconstructionmentioning
confidence: 99%